Raman and ATR-FTIR unmask crystallinity changes and carboxylate group and vinyl group accumulation in natural weathering polypropylene microplastics - Raihan Anshari; Motohiro Tsuboi; Harumi Sato; Kohji Tashiro; Yukihiro Ozaki (Scientific Reports)
Abstract Naturally weathered polypropylene (NWPP) samples are useful for investigating the effects of various degradation factors that cannot be obtained in artificial laboratory experiments. In this study, NWPP samples were extracted from beach sediments (Ashiya, Hyogo, Japan). Raman and attenuated total reflection (ATR)–Fourier-transform infrared (FTIR) spectroscopies were used to analyze variations in the composition, crystallinity, orientation, and degradation of NWPP microplastics. The degree of degradation varies from sample to sample, from position to position in a sample, and the inside surface or outside surface of a sample. Significant intensity variations were observed for Raman bands at 1150 and 842 cm⁻¹, indicating changes in the crystallinity and molecular orientation of NWPP due to degradation. The Raman spectra of the elongated pristine PP showed intensity increases at 1150, 998, and 842 cm−1, indicating variations in the molecular orientation of the polymer chains induced by elongation. The ATR-FTIR spectra of NWPP yield several major new features in the 3600 –3200 cm−1 (OH stretching), 1750–1500 cm−1 (C=O/C=C/COO− stretching), and 1150–900 cm−1 (C–O/C–C stretching) regions. Of particular note is that in the 1750–1500 cm−1 region, at least four bands due to two kinds of vinyl groups and two kinds of carboxylate groups are clearly observed in the second derivative spectra, while bands arising from carbonyl compounds are weak. This may be the first time that the carboxylate bands have ever appeared more strongly than the carbonyl bands in the IR spectra of NWPP. The appearance of the carboxylate bands indicates two possibilities: one is the effect of seawater on the degradation of NWPP samples, and another is the oxidation of keto groups to the carboxylates. Moreover, since a few kinds of vinyl compounds and carboxylates are produced, it is very likely that the degree of degradation is high in the NWPP samples. In this way, IR spectroscopy is useful for exploring the degradation of NWPP while Raman spectroscopy is effective for examining variations in their crystallinity and orientation.